2019
DOI: 10.1007/s10815-019-01429-6
|View full text |Cite
|
Sign up to set email alerts
|

For whom the egg thaws: insights from an analysis of 10 years of frozen egg thaw data from two UK clinics, 2008–2017

Abstract: Purpose To better understand the characteristics of patients who returned to thaw their frozen eggs to attempt conception and their outcomes. Methods A retrospective analysis of clinical records for all own egg thaw patients in two UK fertility clinics across 10 years, 2008-2017. Results There were 129 patients who returned to thaw their eggs, of which 46 had originally frozen their eggs for social reasons and 83 for a variety of clinical, incidental, and ethical reasons (which we have called Bnon-social^). Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 36 publications
(46 reference statements)
2
37
1
1
Order By: Relevance
“…This reinforces the previous well‐known observation that storing oocytes earlier optimizes outcomes, with the highest probability of a live birth seen before the age of 34 years . The average age at SEF was 37 in this study, which is similar to studies that have been undertaken in Australia, Belgium, Spain, the UK, and the USA, where the average age ranges from 36.5 to 38 years. This demonstrates that women undergoing SEF globally appear to be doing it too late, which may subsequently result in future suboptimal outcomes when they return to use their oocytes.…”
Section: Discussionsupporting
confidence: 90%
“…This reinforces the previous well‐known observation that storing oocytes earlier optimizes outcomes, with the highest probability of a live birth seen before the age of 34 years . The average age at SEF was 37 in this study, which is similar to studies that have been undertaken in Australia, Belgium, Spain, the UK, and the USA, where the average age ranges from 36.5 to 38 years. This demonstrates that women undergoing SEF globally appear to be doing it too late, which may subsequently result in future suboptimal outcomes when they return to use their oocytes.…”
Section: Discussionsupporting
confidence: 90%
“…Be it for medical or non-medical reasons, egg freezing has led to heated debates among experts and the broader public alike. Scholars have in this context extensively explored ethical issues [ 5 , 14 , 17 19 ] and women’s motivations to engage in egg freezing [ 20 , 24 , 25 ]. In this study, empirical-ethical research was used to identify the viewpoints of women in Austria on egg freezing by asking them to reflect in depth upon the issues involved.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of egg freezing as a fertility preservation method has furthermore been addressed from various social science disciplines. Users’ profiles as well as their motivations to engage in egg freezing have been explored in various contexts [ 20 24 ]. As has been shown in previous research, women who engage in egg freezing are mostly single and in a period of their life when their fertility has already started to decline [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most media coverage of oocyte cryopreservation has suggested that women are willing to pay for this new ART treatment to intentionally ‘delay,’ ‘defer’ or ‘postpone’ their fertility, especially for educational and career purposes, thereby achieving reproductive autonomy ( Goldman and Grifo, 2016 ) and forestalling age-related decline in fertility ( Argyle et al, 2016 ). However, recent surveys and ethnographic studies carried out among diverse women in the USA ( Brown and Patrick, 2018 ; Carroll and Kroløkke, 2018 ; Greenwood et al, 2018 ; Hodes-Wertz et al, 2014 ), UK ( Baldwin, 2017 , Baldwin, 2018 ; Baldwin et al, 2015 , Baldwin et al, 2019 ; Gürtin et al, 2019 ; Waldby, 2015 , Waldby, 2019 ), Belgium ( Stoop et al, 2015 ), Australia ( Hammarberg et al, 2017 ; Pritchard et al, 2017 ) and Turkey ( Göçmen and Kiliç, 2018 ; Kiliç and Göçmen, 2018 ) show that ‘lack of a partner’ is cited as the primary reason for oocyte cryopreservation among more than 80% of women across all studies.…”
Section: Extended Questsmentioning
confidence: 99%